Numbers and distribution of eagles in the Czech Republic: reason for optimism - Tomáš Bělka; David Horal (Пернатые хищники и их охрана)
At present, four eagle species are regular breeders in the Czech Republic: White Tailed Sea-Eagle (Haliaeetus albicilla), Eastern Imperial Eagle (Aquila heliaca), Lesser Spotted Eagle (Aquila [Clanga] pomarina), and Golden Eagle (Aquila chrysaetos). There is also a historical record of confirmed breeding of Greater Spotted Eagle (Aquila [Clanga] clanga) in 1847 in the region of Eastern Bohemia. At present, this species is only a rare visitor on autumn and spring passage.